A Literature Study on The Development of Tourism Villages in Indonesia: A Community-Based Approach - Anisa Putri Kusumaningrum; Kumba Digdowiseiso; Yusnita Yusof (CV ODIS, 2023)
This research reviews literature studies on the development of tourist villages in Indonesia using the Community-Based Tourism (CBT) approach. Village Tourism is one of the efforts to develop a sustainable tourism sector, involving the active participation of local communities in the development process, and encouraging the preservation of local culture and nature. This literature study provides an overview of the development of the CBT concept in Indonesia, examines the factors that influence the success of tourist villages, and identifies the economic, social and environmental benefits that can be obtained through this approach. The results of this literature study show that the development of community-based tourism villages can make a positive contribution to local development, cultural preservation and sustainable development in Indonesia. Nevertheless, Challenges such as lack of managerial capacity and access to resources need to be addressed to improve the sustainability of tourism villages in the future. This study provides important insights for parties interested in developing sustainable tourism in Indonesia and similar countries.